Otimização da produção de β-xilosidase por Aspergillus fumigatus - Vieira, Fabíola Giovanna Nesello (2014)
The abundant lignocellulosic biomass in agro-industrial waste can be reused as an inexpensive substrate for inducing the production of enzymes such as β-xylosidases. The purpose of this study was to analyze the production of β-xylosidase from Aspergillus fumigatus (PC-7S-2 M), isolated from the Atlantic Forest of the Dog Head State Park (Paraná, Brazil) and later identified by morphological and molecular (ITS) methods. The mesophilic fungus was grown at 28 °C in liquid culture media containing Czapeck and 1% of different agroindustrial residues (w/v): passion fruit peel, Ponkan peel, barley brewing residue, soy flakes and ripe banana peel. Inoculants of 105 conidia ml-1 were incubated for 7 days, filtered and assayed for β-xylosidase intracellular activity obtaining a maximum value of 15 U ml-1 of the enzyme in the presence of barley brewing residue after 4 days of cultivation. Then, it was used a Central Composite Rotational Design (CCRD) to optimize the production of β-xylosidase, using barley brewing residue as carbon source at a significance level of p<0.10 which generated a predicted model of 245.04 U ml-1. Model validation provided an average optimized result equal to 229.06 U ml-1 for the enzyme. Thus, the production of β-xylosidase increased in 1,500% over the initially obtained for A. fumigatus in the presence of the barley brewing residue, therefore, achieving 93.47% of the predicted model. This finding emphasizes the availability of A. fumigatus β-xylosidase production with possible applications in several biotechnological process.